Strategi Peningkatan Kompetensi Calon Pekerja Migran Indonesia - Fitriani, Desi; Ramdhan, Dadang; Hapsari, Andriyani (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2023)
Prospective Indonesian Migrant Workers (Pekerja Migran Indonesia/PMI) who will work abroad are required to have working competence. Lacks of such competence on prospective migrant workers will potentially result in issues such as discrimination, exploitation, fraud, unpaid salaries, and human trafficking. This article aims to understand strategies which could be conducted by the government and related stakeholders to improve the competence of prospective migrant workers as well asidentify the success factors, obstacles and challenges in the advancement process. The analysis employs a qualitative approach with the method of a literatures study on articles/journals, books, news, regulations related to migrant workers, documents, and other data from the internet. The type of research used is qualitative with a literature study method sourced from articles/journals, books, news, laws related to migrant workers, documents, and the internet. Findings show that a potential strategy to increase working competences for PMI is a job training which includes language skills and digital literacy, APBD allocation, and Final Debriefing of Departure (PAP). Through developing workers’ competences, it is expected that prospective migrant workers will be able to compete well in the global labor market.